Phase-controlled Photonic Quantum Circuits in Laser Written Integrated Optics - Thomas-Peter, N; Smith, B; Kundys, D; Smith, P; Walmsley, I; IEEE (2010)
We present a direct UV-written integrated photonic circuit with on-chip phase control through a thermo-optic phase shifter. An arbitrary beam splitter and a two-photon NOON state are demonstrated with high visibility interference. © 2010 Optical Society of America.